Durabilitas Mortar Polimer Termodifikasi Alami dengan Amylum dan Bahan Tambah Madu - Nanda Isdian Prasetyo; Gerald Arsa Adhiyaksa Abiyoga; Rr. M.I. Retno Susilorini; Budi Santosa (G-SMART, 2018)
The research aimed to investigate the durability of natural modified polymer mortar with amylum and honey admixture of aggressive environment that was modeled by 3 curing media, sea water, brakish water, and tidal flooding water. There were 855 specimens of mortar cubes with addition of amylum of 0,1%, 0,2%, 1%, 2%, and 5% and also honey of  0%, 0,03%, and 0,03%. All specimenswere cured and distributed into 3 curing medias for 7, 14, and 28 days. The result of this research met conclusion that optimum compressive strength was achieved by specimen with composition 0,1%  amylum and  0,03% honey that was cured by sea water.